2022
DOI: 10.1039/d1nr07505e
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of voltage-gated spin Hall nano-oscillators

Abstract: We demonstrate an optimized fabrication process for electric field (voltage gate) controlled nano-constriction spin Hall nano-oscillators (SHNOs), achieving feature sizes of <30 nm with easy to handle ma-N 2401 e-beam...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…The samples were then coated with 40 nm of hydrogen silsesquioxane (HSQ) negative tone electron beam resist. The SHNO chains used in the experiments were then fabricated using a combination of e-beam lithography (Raith EBPG 5200) and Ar-ion etching: more details can be found in ref . The top contact pads are fabricated using laser writing-based direct lithography followed by deposition of Cu­(800 nm)/Pt­(20 nm) thin films for the Ground-Signal-Ground coplanar waveguide.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples were then coated with 40 nm of hydrogen silsesquioxane (HSQ) negative tone electron beam resist. The SHNO chains used in the experiments were then fabricated using a combination of e-beam lithography (Raith EBPG 5200) and Ar-ion etching: more details can be found in ref . The top contact pads are fabricated using laser writing-based direct lithography followed by deposition of Cu­(800 nm)/Pt­(20 nm) thin films for the Ground-Signal-Ground coplanar waveguide.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, we study mutual synchronization in much longer SHNO chains of up to 50 serially connected nanoconstrictions fabricated from W­(5 nm)/CoFeB­(1.4 nm)/MgO­(2 nm), W­(5 nm)/NiFe­(3 nm), and NiFe­(5 nm)/Pt­(5 nm) , material stacks (the order represents the actual stack sequence), focusing primarily on the W based SHNOs with their much lower threshold current and lower line width compared to Pt based systems (due to reduced spin pumping and lower inverse spin Hall effect). We find that robust and complete mutual synchronization can persist in chains of up to 21 oscillators, resulting in 1/ N reduction in line width and N 2 enhanced output peak power compared to single SHNOs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 39 ] Recently, they further studied mutual synchronization in much longer SHNO chains of up to 50 serially connected nano‐constrictions. [ 40 ] They found that robust and complete mutual synchronization can persist in chains of only up to 21 oscillators, resulting in a significantly lower linewidth and higher output power. For synaptic functionalities, magnetic DW devices are the most‐studied spintronic device, owing to its linear magnetization dynamics.…”
Section: Spintronic Devices For Neuromorphic Applicationsmentioning
confidence: 99%
“…Spin-orbit torques (SOTs) in ferromagnetic/heavy metal (FM/HM) heterostructures have emerged as a powerful tool for a wide range of spintronic applications. [1][2][3][4][5][6] Large anti-damping SOTs are of utmost interest and play a pivotal role in ultrafast magnetization switching, [3,7] spintronic oscillators, [4,6,[8][9][10] as well as the emerging area of spintronic-based neuromorphic computing. [11][12][13][14][15] In the FM/HM system, the SOT is generated either via the spin Hall effect [16][17][18][19] from the HM layer and/or the Rashba-Edelstein effect [20,21] from the interface between the DOI: 10.1002/qute.202300092 FM and HM layers.…”
Section: Introductionmentioning
confidence: 99%